L'educazione permanente. Sfide e innovazioni per un sistema di rete territoriale - Chianese, Gina (Educazione per tutta la vita - Open Access, 2016)
The first part of the book illustrates the concept of Lifelong Learning ("Educazione Permanente") with special focuses on the transformative learning, the lifedeep learning and the practice of work based learning. The second part of the book opens with an analysis of the concept of Lifelong Learning in the territory of the Alto Adige-Südtirol through the description of operators, organizations, activities and opportunities, regulatory and implementation aspects - and a survey specifically conducted.